Negative feedback in the bone morphogenetic protein 4 (BMP4) synexpression group governs its dynamic signaling range and canalizes development - Paulsen, Malte; Legewie, Stefan; Eils, Roland; Karaulanov, Emil; Niehrs, Christof (Proceedings of the National Academy of Sciences of the United States of America, 2011)
What makes embryogenesis a robust and canalized process is an important question in developmental biology. A bone morphogenetic protein (BMP) morphogen gradient plays a key role in embryonic development, and we are beginning to understand how the self-regulating properties of its signaling circuitry ensure robust embryonic patterning. An unexplored question is why the BMP signaling circuit is organized as a modular synexpression group, with a prevalence of feedback inhibitors. Here, we provide evidence from direct experimentation and mathematical modeling that the synexpressed feedback inhibitors BAMBI, SMAD6, and SMAD7 (i) expand the dynamic BMP signaling range essential for proper embryonic patterning and (ii) reduce interindividual phenotypic and molecular variability in Xenopus embryos. Thereby, negative feedback linearizes signaling responses and confers robust patterning, thus promoting canalized development. The presence of negative feedback inhibitors in other growth factor synexpression groups suggests that these properties may constitute a general principle.
Gesehen am 29.09.2022